Global Profiling of Phosphorylation Reveals the Barley Roots Response to Phosphorus Starvation and Resupply - Ma, Zengke; Wang, Juncheng; Li, Chengdao; Ren, Panrong; Yao, Lirong; Li, Baochun; Meng, Yaxiong; Ma, Xiaole; Si, Erjing; Yang, Ke; Shang, Xunwu; Wang, Huajun (Frontiers in Plant Science, 2021)
Phosphorus (P) deficiency is a major threat to the crop production, and for understanding the response mechanism of plant roots, P stress may facilitate the development of crops with increased tolerance. Phosphorylation plays a critical role in the regulation of proteins for plant responses to biotic and abiotic stress; however, its functions in P starvation/resupply are largely unknown for barley (Hordeum vulgare) growth. Here, we performed a global review of phosphorylation in barley roots treated by P starvation/resupply. We identified 7,710 phosphorylation sites on 3,373 proteins, of which 76 types of conserved motifs were extracted from 10,428 phosphorylated peptides. Most phosphorylated proteins were located in the nucleus (36%) and chloroplast (32%). Compared with the control, 186 and 131 phosphorylated proteins under P starvation condition and 156 and 111 phosphorylated proteins under P resupply condition showed significant differences at 6 and 48 h, respectively. These proteins mainly participated in carbohydrate metabolism, phytohormones, signal transduction, cell wall stress, and oxidases stress. Moreover, the pathways of the ribosome, RNA binding, protein transport, and metal binding were significantly enriched under P starvation, and only two pathways of ribosome and RNA binding were greatly enriched under Pi resupply according to the protein–protein interaction analysis. The results suggested that the phosphorylation proteins might play important roles in the metabolic processes of barley roots in response to Pi deficiency/resupply. The data not only provide unique access to phosphorylation reprogramming of plant roots under deficiency/resupply but also demonstrate the close cooperation between these phosphorylation proteins and key metabolic functions.